2016
DOI: 10.1002/jca.21493
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided peripheral venous access for therapeutic apheresis procedures reduces need for central venous catheters

Abstract: Therapeutic and donor apheresis requires adequate vascular access to achieve inlet flow rates of ∼50-100 mL/min. While central dialysis-type venous catheters can usually provide such access, their use includes several associated risks. Some of these risks can be avoided or diminished if adequate peripheral venous access can be established. Some patients have adequate peripheral veins for apheresis that cannot be readily identified visually or by palpation. We hypothesized that ultrasound-guided peripheral veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…This result may suggest that, if possible, peripheral veins should be used as vascular access for leukocytapheresis in adult patients not only because the CE1 of MNCs was improved but also to avoid risks associated with central line placement . Knowledge of experienced nurses is important when evaluating vascular access in these donors as well as the implementation of ultrasound‐guided placement of peripheral venous access …”
Section: Discussionmentioning
confidence: 99%
“…This result may suggest that, if possible, peripheral veins should be used as vascular access for leukocytapheresis in adult patients not only because the CE1 of MNCs was improved but also to avoid risks associated with central line placement . Knowledge of experienced nurses is important when evaluating vascular access in these donors as well as the implementation of ultrasound‐guided placement of peripheral venous access …”
Section: Discussionmentioning
confidence: 99%
“…The risks of peripheral vascular access include hematoma formation, nerve damage, patient discomfort, and sclerosis of veins or arteries . In individuals with nonpalpable or difficult vascular anatomy, an ultrasound can aid in establishing peripheral vascular access . Single‐institutional experiences with ultrasound demonstrated that peripheral vein cannulations increased with a reduction in the placement of CVCs …”
Section: Options For Intravascular or Implantable Access Devicesmentioning
confidence: 99%
“…Other studies reported that peripheral venous access was always considered before CVC placement; however, <5% of apheresis procedures were performed using peripheral veins . A recently published study showed how ultrasound guidance prevented CVC when implemented in part of the apheresis department . In this study, we included the whole department and present a systematic training program for the implementation.…”
Section: Discussionmentioning
confidence: 99%